2015
DOI: 10.1176/appi.ps.201400029
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Mental Health Treatment Among Persons With PTSD: Results of a Nationally Representative Survey

Abstract: Objective Despite continued outreach efforts, levels of mental healthcare utilization for posttraumatic stress disorder (PTSD) remain low. As such, it is important to identify factors that may promote or discourage treatment engagement. The current study was designed to examine the association between perceived social support and utilization of several types of PTSD services. Methods Data come from the second wave of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), which was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Findings that being non-Latino black and having less education were associated with a lower odds of treatment utilization among adults with past-year PTSD are similar to the findings for lifetime PTSD and lifetime treatment-seeking in the NCS-R by Wang et al [4] and in other nationally-representative studies [15, 17, 19]. The disparity in access to mental health treatment for PTSD for non-Latino blacks is reflective of a wide body of research documenting differential access to mental and general health services due to racial disparities [40, 41], and further emphasizes the need for policies and programs that address the social inequalities, such as differential access to housing and educational resources, that may underpin these and other findings [42].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Findings that being non-Latino black and having less education were associated with a lower odds of treatment utilization among adults with past-year PTSD are similar to the findings for lifetime PTSD and lifetime treatment-seeking in the NCS-R by Wang et al [4] and in other nationally-representative studies [15, 17, 19]. The disparity in access to mental health treatment for PTSD for non-Latino blacks is reflective of a wide body of research documenting differential access to mental and general health services due to racial disparities [40, 41], and further emphasizes the need for policies and programs that address the social inequalities, such as differential access to housing and educational resources, that may underpin these and other findings [42].…”
Section: Discussionsupporting
confidence: 86%
“…The disparity in access to mental health treatment for PTSD for non-Latino blacks is reflective of a wide body of research documenting differential access to mental and general health services due to racial disparities [40, 41], and further emphasizes the need for policies and programs that address the social inequalities, such as differential access to housing and educational resources, that may underpin these and other findings [42]. Similar to findings from Sripada et al in the National Epidemiological Survey of Alcohol and Related Conditions (NESARC) [19], we found that being in the workforce or seeking work as compared to not being in the workforce were associated with both a lower odds of treatment utilization and a higher odds of unmet treatment need. That individuals in the workforce were both less likely to utilize treatment and more likely to report an unmet need for treatment suggests that structural barriers related to being in the workforce, rather than a lower perception of need, may be underlying reasons for differential utilization of mental health resources for this group.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although the relationship between social support and mental health conditions tends to be relatively consistent, findings on the relationship between social support and mental health service utilization remain equivocal [52,[65][66][67][68][69][70][71]. Social networks and perceived social support may have both stress-reducing functions (reducing the psychological impact of stress) and positive referral functions (encouraging treatment when it is needed) [63].…”
Section: Introductionmentioning
confidence: 99%